Obstructive Sleep Apnea Impacts Cardiac Function in Dilated Cardiomyopathy Patients Through Circulating Exosomes - Gong, Hui; Lyu, Xing; Dong, Lini; Tan, Shengyu; Li, Shizhen; Peng, Jieting; Liu, Yang; Zhang, Xiangyu (Frontiers in Cardiovascular Medicine, 2022)
Background: Obstructive sleep apnea (OSA) is common and independently associated with heart failure. This study aimed to investigate the impact of OSA on heart function in patients with dilated cardiomyopathy (DCM) as well as the possible mechanism related to exosomes regulated autophagy. Methods and Results: A total of 126 patients with DCM who underwent sleep evaluations were analyzed retrospectively. Cardiomyocytes were treated with exosomes isolated from untreated OSA patients and healthy controls. Fibrotic and hypertrophic markers were evaluated, and Akt/mTOR pathway-mediated autophagy was investigated. DCM patients with severe OSA had larger right ventricular end-diastolic diameter (RVEDd) and right atrial diameter (RAD) and increased N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels than DCM patients without OSA. Moreover, NT-proBNP and diabetes mellitus were independently correlated with the apnea-hypopnea index in multiple linear regression analysis. Treatment with OSA-derived exosomes significantly increased Col1A1, ANP, and BNP protein expression and decreased the expression of the autophagy markers LC3B II/I and beclin1. Rapamycin treatment significantly increased the levels of autophagy inhibition and attenuated the increased expression of Col1A1, ANP and BNP induced by OSA-derived exosomes. Conclusion: The severity of OSA is significantly associated with cardiac injury and remodeling. The underlying mechanism may be related to changed autophagy levels, which are regulated by circulating exosomes via the Akt/mTOR signaling pathway. This study may provide a new clue for the treatment of heart failure with OSA.